PENGARUH MANAJEMEN LABA, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN (Studi Emperis pada Perusahaan Sektor Finansial yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023) - Gusti Ayu Putu Wulan Rahmasari; Ni Putu Lia Perdana Sari (Yayasan Nusantara Hasana Berdikari, 2024)
This study examines the effect of earnings management, managerial ownership, independent commissioners and audit committees on firm value using financial sector companies listed on the Indonesia Stock Exchange (IDX). The method used in this study is purposive sampling method and the sample that has met the criteria is 150 samples during the period 2021-2023. The data analysis method in this study uses multiple linear regression analysis techniques. The results showed that earnings management, managerial ownership and audit committee have a negative influence on firm value. In contrast, independent commissioners have a positive influence on firm value.